Social Security and Unsecured Debt - Erik Hurst; Paul Willen (Federal Reserve Bank of Boston, 2004)
Most young households simultaneously hold both unsecured debt on which they pay an average of 10 percent interest and social security wealth on which they earn less than 2 percent. We document this fact using data from the Panel Study of Income Dynamics. We then consider a life-cycle model with 'tempted' households, who find it impossible to commit to an optimal consumption plan and 'disciplined' households who have no such problem, and we explore ways to reduce this inefficiency. We show that allowing households to use social security wealth to pay off debt while exempting young households from social security contributions (but in both cases requiring higher contributions later) leads to increases in welfare for both types of households and, for disciplined households, to significant increases in consumption and saving and reductions in debt.
Keywords: 330; Gesetzliche Rentenversicherung; Lebenszyklus; Private Verschuldung; Verbraucherkredit; Schätzung; USA